Is the Baby to Blame? An Inquiry into the Consequences of Early Childbearing - Azevedo, Joao Pedro; Lopez-Calva, Luis F.; Perova, Elizaveta (World Bank, Washington, DC, 2012)
Teenage pregnancy has been a cause of concern for policy makers because it is associated with a complex and often adverse social context for women. It is seen as the cause of lower social and economic achievement for mothers and their children, and as the potential determinant of inter-generational poverty traps. However, the question of whether pregnancy -- and the subsequent rearing of a child -- is actually the trigger of poverty, higher dependence on social welfare and/ or other undesirable social and economic consequences has not been studied in developing countries with enough rigor to establish a causal relation. This paper follows a methodology previously applied in the United States, using Mexican data from the National Survey of Demographic Dynamics, to exploit information about miscarriages as an instrument to identify the long-term consequences of early child bearing. Thus, the paper takes the advantage of a natural experiment: it compares the outcomes of women who became pregnant in adolescence, and gave birth, to outcomes of women who became pregnant in adolescence and miscarried. This approach only allows for estimating the costs of adolescent childbearing for teenagers in a risk group, that is, teenagers who are likely to experience a pregnancy. The results are consistent with findings in the United States, suggesting that, contrary to popular thinking, adolescent childbearing does not hamper significantly the lifelong opportunities of the young mothers. Actually, women who gave birth during their adolescence have on average 0.34 more years of education, and are 21 percentage points more likely to be employed, compared with their counterparts who miscarried. The results also suggest, however, greater dependence on social welfare among women who gave birth during adolescence: their social assistance income is 36 percent higher, and they are more likely to participate in social programs, especially the conditional cash transfer program Oportunidades.